Low-temperature, shallow-water hydrothermal vent mineralization following the recent submarine eruption of Tagoro volcano (El Hierro, Canary Islands) - González, Javier (2022)
Hydrothermal iron (Fe)-rich sediments were recovered from the Tagoro underwater volcano (Central Atlantic) that formed during the 2011–2012 volcanic event. Cruises in 2012 and 2014 enabled the monitoring and sampling of the early-stage establishment of a hydrothermal system. Degassing vents produced acoustic flares imaged on echo-sounders in June 2012, four months after the eruption. A novel hydrothermal vent system was discovered and sampled in 2014 during a ROV dive. The system is characterized by hornito-like structures and chimneys showing active CO2 degassing and anomalous temperatures at 120–89 m water depth, and along the SE flank at 215-185 m water depth associated with secondary cones. Iron- and silica-rich gelatinous deposits pooled over and between basanite in the hornitos, brecciated lavas, and lapilli. The low temperature, shallow water hydrothermal system was discovered by the venting of Fe-rich fluids that produced a seafloor draped by extensive Fe-flocculate deposits precipitated from the neutrally buoyant plumes located along the oxic/photic zone at 50-70 m water depths. The basanite is capped by mm- to cm-thick hydrothermally derived Fe-oxyhydroxide sediment, and contains micro-cracks and degasification vesicles filled by sulfides (mostly pyrite). Mineralogically, the Fe-oxyhydroxide sediment consists of proto-ferrihydrite and ferrihydrite with scarce pyrite at their base. The Fe-rich endmember contains low concentrations of most trace elements in comparison with hydrogenetic ferromanganese deposits, and the sediments show some dilution of the Fe oxyhydroxide by volcanic ash. The Fe-oxyhydroxide phase, with a mean particle size of 3–4 nm, low average La/Fe ratios of the mineralized deposits from the various sampling sites, and the positive Eu anomalies indicate rapid deposition of the Fe oxyhydroxide near the hydrothermal vents. Electron microprobe studies show the presence of various organomineral structures, mainly twisted stalks and sheaths covered by iron-silica deposits within the mineralized samples, reflecting microbial iron-oxidation from the hydrothermal fluids. Sequencing of 16 s rRNA genes also reveals the presence of other microorganisms involved in sulfur and methane cycles. Samples collected from hornito chimneys contain silicified microorganisms coated by Fe-rich precipitates. The rapid silicification may have been indirectly promoted by microorganisms acting as nucleation sites. We suggest that this type of hydrothermal deposit might be more frequent than presently reported to occur in submarine volcanoes. On a geological scale, these volcanic eruptions and low-temperature hydrothermal vents might contribute to increased dissolved metals in seawater, and generate considerable Fe-oxyhydroxide deposits as identified in older hot-spot seamounts.